2021
DOI: 10.3389/fimmu.2021.689697
|View full text |Cite
|
Sign up to set email alerts
|

A Reproducible Bioprinted 3D Tumor Model Serves as a Preselection Tool for CAR T Cell Therapy Optimization

Abstract: Chimeric antigen receptor (CAR) T cell performance against solid tumors in mouse models and clinical trials is often less effective than predicted by CAR construct selection in two-dimensional (2D) cocultures. Three-dimensional (3D) solid tumor architecture is likely to be crucial for CAR T cell efficacy. We used a three-dimensional (3D) bioprinting approach for large-scale generation of highly reproducible 3D human tumor models for the test case, neuroblastoma, and compared these to 2D cocultures for evaluati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…In a model composed of the neuroblastoma cell line SH-SY5Y in co-culture with mesenchymal stromal cells and human primary umbilical vein endothelial cells, the neuroblastoma cells formed Homer Wright-like rosettes and maintained their proliferative capacities [ 34 ]. Another bioprinted tumor model consisting of SK-N-BE(2) cells was used to investigate the infiltration of chimeric antigen receptor (CAR) T cells into tumor tissues [ 35 ]. In further studies, neuroblastoma cell lines have been used to develop neural tissue for studying neurodegenerative diseases [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a model composed of the neuroblastoma cell line SH-SY5Y in co-culture with mesenchymal stromal cells and human primary umbilical vein endothelial cells, the neuroblastoma cells formed Homer Wright-like rosettes and maintained their proliferative capacities [ 34 ]. Another bioprinted tumor model consisting of SK-N-BE(2) cells was used to investigate the infiltration of chimeric antigen receptor (CAR) T cells into tumor tissues [ 35 ]. In further studies, neuroblastoma cell lines have been used to develop neural tissue for studying neurodegenerative diseases [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described above, the study of Grundwald et al [ 35 ] used a bioprinted neuroblastoma model consisting of SK-N-BE(2) cells to investigate tumor tissue penetration by CAR T cells. Our model, which consists of not only cancerous cells, but also normal fibroblasts, can now be used to investigate the specificity of the treatment for the destruction of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of 3D technology has been more widespread in the adult oncology literature [12,41] and has had only limited reports in pediatric oncology. Pediatric cancer researchers have printed SH-SY5Y neuroblastoma cells to create a neural network [42] and SK-N-BE neuroblastoma cells to study CAR-T cell therapy [43], but to our knowledge, no one has yet reported bioprinting neuroblastoma PDX cells. In the current investigations, we successfully created bioprinted microtumors of the COA6 and COA129 PDXs.…”
Section: Discussionmentioning
confidence: 99%
“… 146 In addition, bioprinted (neuroblastoma) organoids could be used to preselect CAR T cell constructs. 147 There is no standard cytotoxicity assay to test the efficacy of CARs with PDOs. One study established a luciferase-based endpoint assay and a live microscopy assay for continuous and cell-resolved analysis to monitor NK CAR-mediated cytotoxicity against colorectal cancer organoids.…”
Section: Pdac Models To Evaluate Cellular Immunotherapymentioning
confidence: 99%